Potential Regional Pollination Services of Spodoptera litura (Lepidoptera: Noctuidae) Migrants as Evidenced by the Identification of Attached Pollen - Xiaokang Li; Huiru Jia; Dazhong Liu; Xianyong Zhou; Kongming Wu (Plants)
Many species of noctuid moths exhibit long-distance migratory behavior and have an important pollination service function in terrestrial ecosystems. Spodoptera litura (Fabricius) is a globally distributed insect; however, its role in pollination remains underexplored. In this study, the feeding preferences and inter regional pollination of S. litura adults were explored. We conducted pollen analysis on 1253 S. litura migrants captured from 2018 to 2021 on Beihuangcheng Island in the Bohai Strait of China, which is located in the East Asian insect migration path. The results show that an average of 51.1% of S. litura migrants carry plant pollen each year, and the carrying rate shows fluctuations based on sex, year, and season. By combining morphological identification and DNA barcoding, pollen species were identified from 40 species of plants, representing 21 families and 26 genera, mainly from angiosperms of Dicotyledoneae, with Asteraceae, Apocynaceae, and Amaranthaceae being the dominant taxa. The geographical distribution range of Chrysanthemum zawadskii and Adenophora trachelioides and a migration trajectory simulation analysis indicate that S. litura predominantly migrate from Liaoning Province in Northeast China to North China over the Bohai Sea in autumn. These findings indicate the potential pollination activities of S. litura in North China and Northeast China, enriching our understanding of the interaction between S. litura and the plants it pollinates.